Antipsychotics for delirium in the general hospital setting in consecutive 2453 inpatients: a prospective observational study. (25th June 2013) - Hatta, Kotaro; Kishi, Yasuhiro; Wada, Ken; Odawara, Toshinari; Takeuchi, Takashi; Shiganami, Takafumi; Tsuchida, Kazuo; Oshima, Yoshio; Uchimura, Naohisa; Akaho, Rie; Watanabe, Akira; Taira, Toshihiro; et al.
<x xml:space="preserve">Abstract</x> Objective Attention to risk of antipsychotics for older patients with delirium has been paid. A clinical question was whether risk of antipsychotics for older patients with delirium would exceed efficacy of those even in the general hospital setting. Methods A prospective observational study proceeded over a 1‐year period at 33 general hospitals, where at least one psychiatrist worked full time. Subjects were patients who developed delirium during their admission due to acute somatic diseases or surgery, and who received antipsychotics for delirium. The primary outcome was rates and kinds of serious adverse events. Results Among 2834 patients who developed delirium, 2453 patients received antipsychotics, such as risperidone (34%), quetiapine (32%), and parenteral haloperidol (20%), for delirium. Out of 2453 patients, 22 serious adverse events (0.9%) were reported. Aspiration pneumonia was the most frequent (17 patients, 0.7%), followed by cardiovascular events (4 patients, 0.2%) and venous thromboembolism (1 patient, 0.0%). There was no patient with a fracture or intracranial injury due to a fall. No one died because of antipsychotic side effects. The mean Clinical Global Impressions—Improvement Scale score was 2.02 (SD 1.09). Delirium was resolved within 1 week in more than half of the patients (54%). Conclusions In the general hospital setting under management including fine dosage adjustment and early detection of side effects, risk of antipsychotics for older patients with delirium might be low, in contrast to antipsychotics for dementia in the nursing home or outpatient settings. A point may be not how to avoid using antipsychotics but how to monitor their risk. © 2013 The Authors. International Journal of Geriatric Psychiatry published by John Wiley & Sons, Ltd.